Artificial Intelligence Development and Music Education System Reform in the Context of 5G Network. (8th August 2022) - Zhang, Zi; Li, Zhuolin; Pan, Jian; Chen, Wenli; Bai, Qiulin
Abstract : The application of 5G communication technology will help our lives in many ways because the biggest advantage of 5G technology is the ubiquitous wireless connectivity, coupled with the standardization of IP as a data protocol, the availability of low-cost and powerful computing resources in the cloud, and the increased speed of transmitted data, all of which help shape the vision of 5G. Many application scenarios can use lower-cost 5G networks. Based on advances in various communication technologies, several new application scenarios, including robotics and human-robot interaction, are beginning to emerge. Most of the new applications can be realized through 4G networks. To maximize its potential, 5G networks will need to meet a variety of requirements and support the allocation of resources to different applications in an intelligent manner, which is a major technical challenge. As a hot technology in 5G communications, high-density heterogeneous networks have attracted a lot of attention worldwide. This paper firstly discusses the current status of 5G technology research and analyzes the necessity and main features of 5G technology development, so as to gain a deeper understanding of the main features of 5G. This paper then follows a comprehensive discussion of the development of artificial intelligence in the context of 5G networks and its contribution to the reform of the music education system and designs a method for reforming the music teaching system based on artificial intelligence algorithms in the context of 5G networks. The experimental results show that the algorithm of this paper has a good promotion effect on the music education system reform and verifies the effectiveness of the model.